2021
DOI: 10.3390/v13061136
|View full text |Cite
|
Sign up to set email alerts
|

Transduction Enhancers Enable Efficient Human Adenovirus Type 5-Mediated Gene Transfer into Human Multipotent Mesenchymal Stromal Cells

Abstract: Human multipotent mesenchymal stromal cells (hMSCs) are currently developed as cell therapeutics for different applications, including regenerative medicine, immune modulation, and cancer treatment. The biological properties of hMSCs can be further modulated by genetic engineering. Viral vectors based on human adenovirus type 5 (HAdV-5) belong to the most frequently used vector types for genetic modification of human cells in vitro and in vivo. However, due to a lack of the primary attachment receptor coxsacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“… 2 , 30 However, due to the lack of CAR expression, hMSCs are very difficult to transduce with HAdV-5 vectors. As we previously observed that positively charged molecules significantly enhanced HAdV-5-mediated gene transfer into hMSCs, 27 we analyzed transduction of bone marrow-derived (BM-) and adipose tissue-derived (A-) hMSCs with the charge-modified vectors HAdV-5-ΔHVR1, HAdV-5-HexPos2, and HAdV-5-HexPos3. We observed a striking 500-fold increase in mean fluorescence intensity (MFI) of BM-hMSCs after transduction with HAdV-5-HexPos3 compared with HAdV-5 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 2 , 30 However, due to the lack of CAR expression, hMSCs are very difficult to transduce with HAdV-5 vectors. As we previously observed that positively charged molecules significantly enhanced HAdV-5-mediated gene transfer into hMSCs, 27 we analyzed transduction of bone marrow-derived (BM-) and adipose tissue-derived (A-) hMSCs with the charge-modified vectors HAdV-5-ΔHVR1, HAdV-5-HexPos2, and HAdV-5-HexPos3. We observed a striking 500-fold increase in mean fluorescence intensity (MFI) of BM-hMSCs after transduction with HAdV-5-HexPos3 compared with HAdV-5 ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“… 59 , 60 However, ex vivo transduction of hMSCs with HAdV-5-based vectors is very inefficient due to a lack of CAR expression on this cell type. 13 , 27 We recently identified several transduction enhancers that can be used to enhance HAdV-5-mediated gene transfer into hMSCs. 27 However, while transduction enhancers are a readily available adjuvant for in vitro transduction experiments, prior to clinical use, a potential impact on the biology and functionality would need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations